The Staphylococcus-Specific Gene rsr Represses agr and Virulence in Staphylococcus aureus - Tamber, Sandeep (American Society for Microbiology (ASM), 2010)
The expression of virulence factors in Staphylococcus aureus is tightly coordinated by a vast network of regulatory molecules. In this report, we characterize a genetic locus unique to staphylococci called rsr that has a role in repressing two key virulence regulators, sarR and agr. Using strain SH1000, we showed that the transcription of virulence effectors, such as hla, sspA, and spa, is altered in an rsr mutant in a way consistent with agr upregulation. Analysis of RNAIII expression of the agr locus in rsr and rsr-sarR mutants indicated that rsr likely contributes to agr expression independently of SarR. We also provide evidence using a murine model of S. aureus skin infection that the effects mediated by rsr reduce disease progression.